2021
DOI: 10.3389/fmicb.2021.602724
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Efflux Pumps, Mutations in the Pumps’ Regulators, Chromosomal Mutations, and AAC(6′)-Ib-cr Are Associated With Fluoroquinolone Resistance in Diverse Sequence Types of Neonatal Septicaemic Acinetobacter baumannii: A 7-Year Single Center Study

Abstract: This study investigates susceptibility toward three fluoroquinolones (ciprofloxacin, levofloxacin, moxifloxacin), multiple fluoroquinolone-resistance mechanisms, and epidemiological relationship of neonatal septicaemic Acinetobacter baumannii. Previous studies on fluoroquinolone resistance in A. baumannii focused primarily on ciprofloxacin susceptibility and assessed a particular mechanism of resistance; a more holistic approach was taken here. Epidemiological relationship was evaluated by Multi Locus Sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…These affected the QRDRs within GyrA (S83L) and ParC (S80L) enzymes. The mutation pattern identified in our isolates was commonly reported as the predominant mechanism responsible for fluoroquinolones resistance in A. baumannii (Hamed et al, 2018;Nodari et al, 2020;Roy et al, 2021).…”
Section: Discussionsupporting
confidence: 61%
“…These affected the QRDRs within GyrA (S83L) and ParC (S80L) enzymes. The mutation pattern identified in our isolates was commonly reported as the predominant mechanism responsible for fluoroquinolones resistance in A. baumannii (Hamed et al, 2018;Nodari et al, 2020;Roy et al, 2021).…”
Section: Discussionsupporting
confidence: 61%
“…The aac ( 6′ ) -Ib-cr was observed frequently and was present in 14 strains. This gene has spread rapidly among Enterobacterales , and although conferring only low-level resistance, it may create an environment that facilitates the selection of highly resistant determinants, especially in organisms harboring other quinolone resistance determinants ( Roy et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to them, quinolones resistance is more than 90% among Acinetobacter isolates, which is consistent with the present study. 19,20 An interesting finding of our study is a revival of antimicrobial susceptibility to Doxycycline. Sadhu et al reported that Doxycycline has good efficacy against MDR Acinetobacter spp., and its use can be considered as an alternative therapy to downregulate the pressure on other groups of antibiotics.…”
Section: Discussionmentioning
confidence: 82%